Material with structural color and preparation method and application thereof

Through the nanoring self-assembly technology induced by surface tension gradient, the nanoring array is closely arranged using the LB membrane analyzer to solve the problem of uneven orientation of the nanoring array, and achieve high-quality nanoring array preparation and application expansion of structural color materials.

CN119591920AActive Publication Date: 2025-03-11DALIAN UNIV OF TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411644355.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare morphological anisotropic nanoring arrays, resulting in uneven orientation in solution and the inability to form uniform and orderly nanoring arrays, thus limiting the application of structural color materials.

Method used

Through the nanoring self-assembly process induced by surface tension gradient, the nanorings are closely arranged on a transparent substrate using an LB membrane analyzer to form a single layer of nanoring arrays. This method ensures the high quality and orderliness of the nanoring array by controlling the concentration of the nanoring dispersion, the solvent components, the pH of the subphase and the parameters of the LB membrane analyzer.

Benefits of technology

The tight arrangement and uniform transfer of nanoring arrays to the substrate surface are achieved, and materials with structural color effects that change with the observation angle are obtained, which expands the application potential of structural color materials in the fields of anti-counterfeiting, display and encryption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591920A_ABST
    Figure CN119591920A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of optical and nano material self-assembly, and provides a material with structural color as well as a preparation method and application thereof. Polymer nanoring is used as an assembly unit, a volatile organic solvent is used as a dispersion medium, a water-air interface is used as an assembly interface, the nanoring array is directionally arranged on the water surface through a self-assembly process induced by an interface surface tension gradient, the external diameter of the nanoring is 500-1000nm, and the thickness of the nanoring is 100-400nm. And then controllably transferring the closely arranged nanoring array to a transparent substrate under proper film forming pressure, film forming speed, film drawing speed and film drawing pressure by utilizing an LB film analyzer technology to obtain a material with a structural color. The prepared structural color material is obvious in structural color and has angle correlation, meanwhile, the structural color of the structural color material can be adjusted and controlled through the size of the assembly unit, and the structural color material is suitable for being used in the fields of display, anti-counterfeiting, encryption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optics and nano material self-assembly, and relates to a material with structural color and a preparation method and application thereof. Background Art

[0002] The periodic nanoarrays assembled from colloidal particles can interact with light to produce bright, colorful structural colors, also known as structural colors. This type of structural color is different from conventional pigments or dyes. It is environmentally friendly, stable, and insensitive to light. Therefore, it plays an increasingly important role in anti-counterfeiting, display, encryption and other fields.

[0003] According to the morphological characteristics of colloidal particles, nanoarrays can be divided into nanosphere arrays and arrays with morphologically anisotropic nanoparticles as units. Compared with nanosphere arrays, arrays with morphologically anisotropic assembly units can improve the diversity of assembly methods due to the higher morphological complexity of the assembly units, thereby improving the nanoarray's ability to regulate light. Wang et al. reported an ordered assembly composed of elliptical nanoparticles in the article "Magnetic Assembly and Field-Tuning of Ellipsoidal-Nanoparticle-Based Colloidal Photonic Crystals". Due to the asymmetry of the elliptical structure, the periodicity of the assembly in different directions is different, which is a feature that nanosphere assemblies do not have, thus significantly broadening the adjustable range of reflected light. Song et al. reported a nanoarray composed of polyhedron assembly units in the article "Design and Self-Assembly of Polyhedron Particles to Construct Iridescent Structural Colors". Due to the multi-directional scattering properties of the polyhedron, the array exhibits a shining metallic texture structural color. This unique structural color has application potential in the field of anti-counterfeiting. The above studies show that it is necessary to further expand the types of anisotropic nanoparticle assemblies and study the influence of their structure on light transmission, both in the field of theoretical research and in application. However, in general, the current research in this area is very limited, which is mainly attributed to the difficulty of orderly assembly of morphological anisotropic nanoparticles.

[0004] In previous research work (CN112499615A), we reported a morphologically anisotropic nanopolymer ring, nanocarbon ring and its preparation method. Using long-chain fatty alcohol phase change materials, surfactants, phenols, aldehydes and organic amines as raw materials, water as solvent, and low-temperature polymerization, polymer rings with regular morphology and adjustable cross-sectional diameter were prepared. Since these nanoring materials do not have a periodic structure, they do not have structural colors themselves. Based on the principle of structural color generation, it is expected that new structural color materials can be prepared by periodically arranging nanorings, which is of great significance for expanding the application performance and scenarios of structural color materials. However, for nanostructures such as nanorings with anisotropic morphology, the van der Waals force and electrostatic force they are subjected to in the solution are asymmetric, so it is necessary to more accurately control the orientation of the nanorings in order to prepare uniform and ordered nanoring arrays. Due to the existence of the above challenges, there are currently no reports in this regard. Summary of the invention

[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a material with structural color, which is composed of a transparent substrate and a single-layer nanoring array uniformly covering the surface of the substrate. In the nanoring array, the nanorings are closely arranged in a "lying" manner, and the number of nanorings per square millimeter is 800-2000. The structural color material can present a structural color that changes with the observation angle under transmission conditions.

[0006] The second object of the present invention is to provide a method for preparing a material with structural color, the principle of the preparation method is the self-assembly process of nano-rings induced by surface tension gradient.

[0007] The third object of the present invention is to provide a material with structural color for use in the fields of structural color materials, anti-counterfeiting, display and encryption.

[0008] The technical solution of the present invention:

[0009] A material with structural color, mainly composed of a transparent substrate and a single-layer nanoring array uniformly covering the surface of the substrate; in the nanoring array, the nanorings are closely arranged in a "lying" manner, and the number of nanorings arranged per square millimeter is 800-2000. The structural color material can present structural colors that change with the observation angle under transmission conditions.

[0010] A method for preparing a material with structural color comprises the following steps:

[0011] ① Add the nano-rings into a volatile organic solvent and perform ultrasonic vibration to obtain a nano-ring dispersion of a certain concentration;

[0012] ② Use FLB2000A LB film analyzer to prepare materials with structural color: fill the disk of the LB film analyzer with ammonia aqueous solution of a certain pH as a subphase, then clamp the transparent substrate with the mechanical arm of the LB film analyzer and immerse it in the groove located in the center of the disk; slowly drop a certain volume of the above-mentioned nanoring dispersion into the ammonia aqueous solution; the addition of organic solvent will cause an imbalance in the surface tension of the entire water surface. Driven by the unbalanced surface tension, convection will occur on the water surface, and the nanorings will float on the water surface during the convection process to form loose "island-like" nanoring monolayer aggregates; set the parameters of the LB film analyzer (film formation speed, film formation pressure, film pulling speed, film pulling pressure), and then the barriers of the LB film analyzer located at both ends of the disk start to move according to the set film formation speed and compress the nanoring aggregates floating on the water surface into a tightly arranged single-layer nanoring array under the set film formation pressure. Then the robot arm is controlled to pull the transparent substrate upward at the set film pulling speed. At the same time, the barrier will slowly adjust its position to keep the pressure on the nano-ring array at the set film pulling pressure, so that the nano-ring array on the water surface is slowly transferred to the continuously rising substrate. When the substrate is completely exposed to the water surface, the nano-ring array is evenly transferred to the surface of the substrate to obtain a structural color material.

[0013] The outer diameter of the nano ring is 500-1000nm, and the thickness is 100-400nm.

[0014] The volatile organic solvent is propanol, isopropanol, butanol, isobutanol or amyl alcohol, preferably butanol.

[0015] The mass fraction of the nanorings in the nanoring dispersion is 0.5%-3.5%, preferably 2%.

[0016] The pH of the aqueous ammonia solution is between 7.1 and 11.0, preferably 10.0.

[0017] The certain volume of the nano-ring dispersion liquid is 0.2-4 μL of the nano-ring dispersion liquid added per square centimeter of the disk surface.

[0018] The parameters of the LB film analyzer are: film forming pressure of 15-30mN / m; film forming speed of 1mm / min-40mm / min; film drawing speed of 1mm / min-40mm / min; and film drawing pressure of 15-30mN / m.

[0019] The transparent substrate is glass, quartz, PDMS, PET, PP, etc., preferably glass and quartz.

[0020] Beneficial effects of the invention: The present application discloses a material with structural color, a preparation method and an application thereof. The structural color material is obtained by using nanorings as assembly units, and by using a surface tension-induced self-assembly method, through an LB film analyzer, the nanoring array is tightly arranged on a transparent substrate. Appropriate concentration of the nanoring dispersion, solvent components, pH of the subphase, film forming speed, film forming pressure, film drawing speed, and film drawing pressure can avoid the problems of disordered stacking, multi-layer overlap, sparse arrangement, etc. of the nanoring array, and are the key to preparing high-quality nanoring arrays. A better arrangement state of the nanorings is a prerequisite for obtaining bright structural colors. The properties of the structural color can be further adjusted by adjusting the size of the nanorings. The material shows application potential in new structural color materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a microscopic morphology of the nanoring assembly array prepared in Example 1 of the present invention.

[0022] Figure 2 The scattering spectrum of the nano-ring assembly array prepared in Example 1 of the present invention varies with the scattering angle.

[0023] Figure 3 This is a microscopic morphology of the nanoring assembly array prepared in Example 2 of the present invention.

[0024] Figure 4 The scattering spectrum of the nano-ring assembly array prepared in Example 2 of the present invention varies with the scattering angle.

[0025] Figure 5 This is a microscopic morphology of the nanoring assembly array prepared in Comparative Example 1 of the present invention.

[0026] Figure 6 This is a microscopic morphology of the nanoring assembly array prepared in Comparative Example 2 of the present invention.

[0027] Figure 7 This is a microscopic morphology of the nanoring assembly array prepared in Comparative Example 10 of the present invention. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0029] Example 1

[0030] A method for preparing a material with structural color, specifically comprising the following steps:

[0031] ① Add 20 mg of polymer nanorings (outer diameter 850 nm, thickness 250 nm) into 1 mL of butanol and ultrasonically vibrate to obtain a 2 wt% nanoring dispersion;

[0032] ② Use FLB2000A LB film analyzer to prepare structural color materials: Fill the disk of the LB film analyzer with NH4OH aqueous solution of pH=10 as the subphase, then clamp the glass slide with the mechanical arm of the LB film analyzer and immerse it in the groove filled with water in the center of the disk. Slowly drip 200μL of the above nanoring dispersion on the water surface, that is, drip 0.83μL per square centimeter of the disk surface. Set the parameters of the LB film analyzer (film forming speed of 20mm / min, film forming pressure of 20mN / m, film pulling speed of 10mm / min, film pulling pressure of 20mN / m) and start the film forming operation, then the LB film barriers at both ends of the disk start to move at the set film forming speed of 20mm / min and compress the nanoring aggregates floating on the water surface into a tightly arranged single-layer nanoring array under the set film forming pressure of 20mN / m. Then the robot arm is controlled to pull the glass slide upward at the set film pulling speed of 10mm / min, and the barrier is slowly adjusted to stabilize the pressure on the nano-ring array at about 20mN / m, so that the nano-ring array on the water surface is slowly transferred to the continuously lifted glass slide. After the glass slide is completely exposed to the water surface, the nano-ring array is evenly transferred to the surface of the glass slide to obtain a structural color material.

[0033] Figure 1 This is a scanning electron microscope (SEM) image of the nanoring array prepared in Example 1. As can be seen from the image, the nanorings are densely arranged on the glass slide substrate in a "lying" manner.

[0034] Figure 2 This is the scattering spectrum of the nanoring array prepared in Example 1 as the scattering angle (the angle between the scattering angle and the normal direction of the array) changes. It can be seen that as the scattering angle increases (the incident light and the scattered light are on both sides of the array, and the angle between the incident angle and the normal direction of the array is 0°), the scattering peak is always located in the blue light region.

[0035] This orderly array of nanorings is significantly different from the spherical array. First, the nanoring itself has two adjustable dimensions, namely diameter and thickness, so compared with nanospheres, it has more adjustable dimensions and more controllable optical properties. Secondly, when the nanoring array is regarded as a type of grating material, the cavity area inside it and the gap area between the rings exist periodically, forming the effect of a compound grating, which is equivalent to the superposition of two layers of gratings with different structures. Theory shows that compared with ordinary gratings, compound gratings can more effectively change the propagation path of light, thereby achieving a larger diffraction angle. Therefore, this type of nanoring array may play a unique role in image display, signal transmission and other fields in the future.

[0036] Example 2

[0037] A method for preparing a material with structural color, which is different from Example 1 in that: the diameter of the nano ring is 970 nm and the thickness is 440 nm.

[0038] Figure 3 This is a scanning electron microscope (SEM) image of the nanoring array prepared in Example 2. It can be seen from the image that the nanorings are directionally arranged on the glass slide substrate.

[0039] Figure 4 This is the scattering spectrum of the nanoring array prepared in Example 2 as the scattering angle changes. It can be seen that as the scattering angle increases, the scattering peak position redshifts from the green region to the red region, which is significantly different from the structural color of the nanoring array in Example 1. This is because as the size of the nanoring increases, the size of the periodic unit of the array increases, which, according to the grating diffraction formula, will lead to a red shift in the scattering peak.

[0040] Example 3

[0041] A method for preparing a material with structural color, which is different from Example 1 in that the concentration of the nano-cyclobutanol dispersion is 1wt%.

[0042] Example 4

[0043] A method for preparing a material with structural color, which is different from Example 1 in that the solvent of the nano-ring dispersion is isopropanol.

[0044] Example 5

[0045] A method for preparing a material with structural color, which is different from Example 1 in that: the pH of the subphase in the LB film analyzer is 8.

[0046] Example 6

[0047] A method for preparing a material with structural color is different from that of Example 1 in that the volume of the nanoring dispersion added is 500 μL, that is, 2.1 μL is added per square centimeter of the disk surface.

[0048] Example 7

[0049] A method for preparing a material with structural color, which is different from Example 1 in that: the transparent substrate is a PDMS film.

[0050] Example 8

[0051] A method for preparing a material with structural color, which is different from Example 1 in that: the film forming pressure is 28mN / m.

[0052] Comparative Example 1

[0053] The difference between Comparative Example 1 and Example 1 is that the film forming pressure of the LB film analyzer is 40 mN / m.

[0054] Figure 5 The SEM image of the nano-ring array prepared in this comparative example shows that the nano-ring array prepared in this comparative example has obvious multi-layer stacking areas. This is because the pressure applied by the scratch barrier is too large, causing the flexible nano-ring array on the interface to break and stack on each other, forming a large number of irregular stacking structures.

[0055] Comparative Example 2

[0056] The difference between Comparative Example 2 and Example 1 is that the film forming pressure of the LB film analyzer is 10 mN / m.

[0057] Figure 6 The scanning electron microscope (SEM) diagram of the nano-ring array obtained in this comparative example shows that the nano-ring array at this time is randomly distributed on the substrate in the form of "island-like" arranged by different numbers of nano-rings. This is because the pressure applied by the barrier is too small, causing the nano-rings dispersed on the water surface to be unable to be tightly connected into a large-scale monolayer array. The film forming process is a pre-process of the film raising process, and the two jointly guarantee the orderly arrangement of the nano-ring array. Therefore, the film forming pressure needs to be adjusted within a suitable range, and being too large or too small is not conducive to the formation of high-quality nano-ring arrays.

[0058] Comparative Example 3

[0059] The difference between Comparative Example 3 and Example 1 is that the film pulling pressure of the LB film analyzer is 40 mN / m.

[0060] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. The effect of excessive film-drawing pressure and excessive film-forming pressure is similar, both of which will cause the nanoring array to stack on each other due to excessive compression force during the transfer process to the substrate, causing the nanoring array to become disordered.

[0061] Comparative Example 4

[0062] The difference between Comparative Example 4 and Example 1 is that the film pulling pressure of the LB film analyzer is 10 mN / m.

[0063] The nanoring array structure obtained under this condition is very sparsely arranged. The effect of too low film-drawing pressure and too low film-forming pressure is similar. Both will cause the nanoring array to be unable to be tightly connected into a large-scale single-layer array during the transfer process to the substrate due to too little compression force, resulting in a loose structure of the nanoring array. The film-drawing pressure is a decisive factor affecting the quality of the nanoring array during the film transfer process. Both too high and too low pressure will lead to a decrease in the orderliness of the film transferred to the substrate.

[0064] Comparative Example 5

[0065] The difference between Comparative Example 5 and Example 1 is that the film forming speed of the LB film analyzer is 45 mm / min.

[0066] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. If the film formation speed is too high (45mm / min), the floating nanorings on the water surface will quickly overlap and stack, which will easily lead to an imbalance in the interaction force of the local area of ​​the entire nanoring array, resulting in an increase in the number of unneeded stacking areas of the obtained nanoring array, affecting the orderliness of the nanoring array.

[0067] Comparative Example 6

[0068] The difference between Comparative Example 6 and Example 1 is that the film forming speed of the LB film analyzer is 0.5 mm / min.

[0069] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. When the film pulling speed is too slow (0.1mm / min), the barrier compression process will become very slow, and the nanorings will gradually be immersed in the water phase from the interface during a long period of static standing. The nanorings dispersed in the subphase will also be partially pulled to the surface of the glass slide, resulting in a decrease in the orderliness of the nanoring array.

[0070] Comparative Example 7

[0071] The difference between Comparative Example 7 and Example 1 is that the film drawing speed of the LB film analyzer is 50 mm / min.

[0072] The nano-ring array structure obtained under this condition is very sparse. If the film lifting speed is too high (60 mm / min), the nano-ring array will not have sufficient contact time with the substrate to achieve transfer, resulting in a sparse nano-ring array structure.

[0073] Comparative Example 8

[0074] The difference between Comparative Example 8 and Example 1 is that the film drawing speed of the LB film analyzer is 0.1 mm / min.

[0075] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. When the film pulling speed is too low (0.1mm / min), it takes about 50 minutes to prepare a sample as large as a glass slide. The nanorings will gradually be immersed in the water phase from the interface during the long-term static process. The nanorings dispersed in the subphase will also be partially pulled to the surface of the glass slide, resulting in a decrease in the orderliness of the nanoring array.

[0076] Comparative Example 9

[0077] The difference between Comparative Example 9 and Example 1 is that the concentration of the nano-ring dispersion is 0.2 wt %.

[0078] The nano-ring array structure obtained under this condition has a large number of disordered accumulation areas. Comparative Example 2 shows that the nano-rings dispersed on the water surface exist in an "island-like" structure. When the concentration of the nano-ring dispersion is too low (0.2wt%), the nano-rings cannot form this more stable "island-like" structure during the solvent evaporation process, but are more dispersed individually. Therefore, it is easy to sink into the subphase during the subsequent liquid surface disturbance caused by solvent evaporation, and in the subsequent barrier compression process, more defective areas will be generated because the points of action between the rings are more than the points of action between the "islands" and the "islands".

[0079] Comparative Example 10

[0080] The difference between Comparative Example 10 and Example 1 is that the concentration of the nano-ring dispersion is 4.5 wt %.

[0081] Figure 7 The SEM image of the nanoring array prepared in this comparative example shows that there are many irregular accumulations in the nanoring array prepared in this comparative example. This is because when the concentration of the nanoring dispersion is too high, a large number of nanorings are arranged on the water surface at the same time, and the density is too large, causing each nanoring to be interconnected with other surrounding nanorings before reaching a balanced state, so a large number of disordered accumulation areas will be caused.

[0082] Comparative Example 11

[0083] The difference between Comparative Example 11 and Example 1 is that the subphase is an aqueous solution of HCl at pH=4.

[0084] The disordered stacking area of ​​the nanoring array obtained under this condition is significantly increased. This is because pH is a key factor affecting the surface potential of the nanorings. When pH = 4, the surface potential of the polymer nanorings is close to 0. At this time, the electrostatic repulsion between the nanorings is very weak, so it is easy to agglomerate during the arrangement process.

[0085] Comparative Example 12

[0086] The difference between Comparative Example 12 and Example 1 is that the subphase is an aqueous ammonia solution with a pH of 12.

[0087] The disordered stacking area of ​​the nanoring array obtained under this condition is significantly increased. This is because the ammonia concentration is high at this time. Although the potential on the surface of the nanoring increases with the increase of pH, the evaporation of ammonia at this time causes a large disturbance, which is not conducive to the assembly of the nanorings.

[0088] Comparative Example 13

[0089] The difference between Comparative Example 13 and Example 1 is that the solvent in the nanoring dispersion is ethanol.

[0090] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. This is because ethanol is completely miscible with water. Part of the added nanoring ethanol dispersion evaporates on the water surface, driving the nanorings to float on the water surface under the action of surface tension, and the other part is miscible with water, causing the nanorings to be directly dispersed in the subphase. During the film drawing process, this part of the nanorings dispersed in the subphase will also be partially pulled to the surface of the glass slide, resulting in a decrease in the orderliness of the nanoring array.

[0091] Comparative Example 14

[0092] The difference between Comparative Example 14 and Example 1 is that the volume of the nanoring dispersion added dropwise is 6 μL per square centimeter of the disk surface.

[0093] The nanoring array structure obtained under this condition has a large number of disordered stacking areas. This is because the addition of too much nanoring dispersion will cause the area of ​​the single layer arrangement of the nanorings to be larger than the disk area, resulting in disordered stacking of the nanoring array.

Claims

1. A material with structural color, characterized in that: The material with structural color is mainly composed of a transparent substrate and a single-layer nanoring array uniformly covering the surface of the substrate; in the nanoring array, the nanorings are closely arranged in a "lying" manner, and the number of nanorings arranged per square millimeter is 800-2000.

2. The material having structural color according to claim 1, characterized in that: The outer diameter of the nano ring is 500-1000nm, and the thickness is 100-400nm.

3. A method for preparing a material having structural color, characterized in that: The following steps are involved: ① Add the nano-rings into a volatile organic solvent and perform ultrasonic vibration to obtain a nano-ring dispersion of a certain concentration; ② Use FLB2000A LB film analyzer to prepare materials with structural color: fill the disk of the LB film analyzer with ammonia aqueous solution of a certain pH as a subphase, then clamp the transparent substrate with the mechanical arm of the LB film analyzer and immerse it in the groove located in the center of the disk; slowly drop a certain volume of nanoring dispersion into the ammonia aqueous solution to form loose "island-like" nanoring monolayer aggregates; set the film forming speed, film forming pressure, film pulling speed, and film pulling pressure of the LB film analyzer, then the barriers of the LB film analyzer at both ends of the disk start to move according to the set film forming speed and compress the nanoring aggregates floating on the water surface into a tightly arranged single-layer nanoring array under the set film forming pressure; Then the robot arm is controlled to pull the transparent substrate upward at the set film pulling speed, and at the same time the barrier is slowly adjusted to keep the pressure on the nano-ring array at the set film pulling pressure, so that the nano-ring array on the water surface is slowly transferred to the continuously rising transparent substrate; After the transparent substrate is completely exposed to the water surface, the nanoring array is evenly transferred to the surface of the transparent substrate to obtain a material with structural color.

4. The preparation method according to claim 3, characterized in that: The volatile organic solvent is propanol, isopropanol, butanol, isobutanol or amyl alcohol.

5. The preparation method according to claim 3, characterized in that: The mass fraction of the nano-rings in the nano-ring dispersion is 0.5%-3.5%.

6. The preparation method according to claim 3, characterized in that: The pH of the aqueous ammonia solution is between 7.1 and 11.

0.

7. The preparation method according to claim 3, characterized in that: The certain volume of nano-ring dispersion liquid is 0.2-4 μL of the nano-ring dispersion liquid added per square centimeter of the disk surface.

8. The preparation method according to claim 3, characterized in that: The parameters of the LB film analyzer are: film forming pressure of 15-30mN / m; film forming speed of 1mm / min-40mm / min; film drawing speed of 1mm / min-40mm / min; and film drawing pressure of 15-30mN / m.

9. The preparation method according to claim 3, characterized in that: The transparent substrate is glass, quartz, PDMS, PET, or PP.

10. Application of the material with structural color according to claim 1 or 2 in the fields of structural color materials, display, anti-counterfeiting and encryption.

Citation Information

Patent Citations

  • Nano polymer ring, nano carbon ring and preparation method of nano polymer ring and nano carbon ring

    CN112499615A

  • Preparation method of panchromatic structural color or color variation pattern array

    CN103145095A

  • Nanostructures for structural colouring

    CN105723252A

  • Gold nanoring stacked array substrate with surface enhanced Raman scattering and preparation method

    CN107966429A

  • Structural color anti-counterfeiting film based on micro-lens array and preparation method of structural color anti-counterfeiting film

    CN114248504A